Perilaku Perokok Terhadap Kesadaran Kesehatan Lingkungan Dalam Perspektif Fatwa Mui - Musyaffa Amin Ash Shabah; Valisa Nur Ajizah; Uswatun Khasanah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
One of the public health problems is smoking behavior that occurs in various circles of society in Indonesia, including among students or high school students, therefore it is necessary to conduct counseling to provide awareness of the dangers of smoking to health. The purpose of this community service activity is so that students understand efforts to anticipate the catastrophe of smoking on health, also able to disseminate it to the family environment, learning environment and community. The stages of the community service method are carried out with Preparation, Implementation and Evaluation activities. Furthermore, the acquisition of service activities is conveyed descriptively and narratively. The results of the service activities showed that the measurement results before the counseling activities of the participants gave an understanding value of 80.88% from 130 participants. There are 15 question points, the most wrong answer responses to questions related to the catastrophe of smoking, smoking behavior in daily association and activities that are beneficial to support physical health. After the presentation of the material, measurements were made with the same questionnaire before counseling with the aim of knowing the transformation of students' knowledge after getting advice and counseling. The measurement results gave a value of 95.50% from 130 participants. There was an increase in knowledge by 14.62%. It is recommended that the school conduct further guidance in the field of public health on an ongoing basis so that students can be trained to become facilitators or health agents both at school and in their place of residence and also increase the role of school health efforts (UKS) in following up on various health problems that can be handled including smoking at school and according to an Islamic perspective, Smoking law is widespread in today's society, namely makruh. This then motivates smokers to justify their actions assuming acceptance of religion is that in Islam cigarette consumption does not occur including something illegal. As most of you probably know Indonesians follow Islam, which also means the majority of smokers are Muslims. In addition, it was later announced that smoking laws were haram (Purnawan et al. 2022).